Effects of a pain education program in Complementary and Alternative Medicine treatment utilization at a VA medical center. Issue 3 (June 2015) - Cosio, David; Lin, Erica H.
Highlights Veterans may not be fully aware of CAM options available at the VA. Veterans report an overall increase in CAM utilization after completing a education program. Differences in CAM use were found for gender, race, ethnicity, and community. The chiropractor was most utilized modality; hypnosis and aromatherapy were least. Suggestions made for providers in health care systems without an education program.